Soft Robots: Stretchable Polymerized High Internal Phase Emulsion Separators for High Performance Soft Batteries (Adv. Energy Mater. 19/2020). Issue 19 (19th May 2020) - Danninger, Doris; Hartmann, Florian; Paschinger, Werner; Pruckner, Roland; Schwödiauer, Reinhard; Demchyshyn, Stepan; Bismarck, Alexander; Bauer, Siegfried; Kaltenbrunner, Martin
Abstract : The image representing article number 2000467 by Martin Kaltenbrunner and co‐workers shows the mixing of the two phases that form a polyHIPE, a process in which UV‐curable monomers and an electrolyte solution are brought together, to form a highly porous, ion conductive structure. The use of such polyHIPEs as high‐performance separators in stretchable batteries pushes the limits of soft energy sources for autonomous wearables and soft robots.